INTERNATIONAL LAW AND THE ROLE OF THE EUROPEAN UNION AS AN ACTOR IN INTERNATIONAL DISPUTE SETTLEMENT - Mehmeta, Jonida (European Scientific Journal, ESJ, 2015)
This study analyzes the meaning of public international law, international law interaction with European Union law and the perception of the European Union as an international actor in terms of resolving disputes. Debates and numerous theories have been raised about the nature and meaning of public international law, in relation to the rates that it carries, the willingness of states, its binding character and its difference with the European Union. Respect for international law is a primary aim of the Union, which functions on the basis of respecting and guaranteeing this right. In addition to the principles of international law is guaranteed by the Union and the principles on which the European Court of Justice holds the opposite view. The perception of the Union as an important global actor, comes and it strengthened, leaving aside the failures of the Union for resolving disputes and regional and international conflicts. Union has reinforced and create a suitable legal framework and institutional framework to resolve disputes and increase its international role. Increasing the role of the Union is reinforced through the Common Foreign and Security Policy which aims to establish peace, security, stability and conflict resolution.